Dynamics of electron internal transport barrier formation at the H–L transition on EAST. (1st June 2022) - Han, X.; Liu, Y.; Zhou, T.F.; Zhang, T.; Shi, T.H.; Li, Y.Y.; Yuan, Y.; Mao, S.T.; Jin, Y.F.; Wu, X.H.; Wang, S.X.; Yang, Y.; et al.
Abstract: The dynamics of electron-internal transport barrier (e-ITB) formation is studied in the hybrid plasma of neutral beam injection and lower hybrid wave heating on EAST. The e-ITB is observed to be repetitively formed at the H–L transition, where the relaxation process of core radiation triggers an increase in neutron yield and core electron temperature. A reversed q -profile is beneficial for generating the barrier, identified by the appearance of reversed shear Alfvén eigenmodes (RSAEs). The dimensionless parameter of the normalized Larmor radius ( ρ T e * ) is estimated to visualize the dynamic behavior of the e-ITB. It is found that the e-ITB forms once the electron ρ T e * exceeds 0.014, and the RSAEs are accompanied by the e-ITB formation. The barrier foot moves inwards until the L–H transition occurs, where the H-mode pedestal or type-I edge localized mode (ELM) strongly influences the e-ITB intensity. The results of thermal transport modeling show a significant reduction in the core thermal transport coefficient in the electron channel while maintaining a nearly unchanged ion transport level as the e-ITB evolves.